Estratégias para melhoria da produção de ácido clavulânico por Streptomyces clavuligerus - Costa, Cecília Ladeira Lopes (Universidade Federal de São Carlos, 2014)
Clavulanic acid (CA) produced by Streptomyces clavuligerus, is a potent inhibitor of beta-lactamases used in combination with conventional beta-lactam antibiotics in the treatment of infections caused by resistant bacteria to these antibiotics. The biosynthesis of CA is limited by high concentrations of carbon source and like other beta-lactam compounds, it is highly unstable in acidic or basic pHs even at moderate temperatures. In this work, it was investigated different strategies to improve the production of AC. Batch and batch cultivations with glycerol pulses were carried out in shaker at 250 rpm and pH 6.8 at constant temperatures of 20, 25 and 30°C (run control), as well as with temperature reduction after cell growth phase from 30 to 25°C, 30 to 20°C and 25 to 20 C. It was also investigated the effects of temperature and pH on the AC degradation at various cultivation times in the presence of different concentration of ammonium ion. It was observed that the use of low temperatures (20°C) during cultivation reduced the substrate uptake rate and provides a higher accumulation of AC, in the broth by reducing the effects of CA degradation and inhibition effects caused by carbon source. Batch cultivations with higher glycerol concentration (30 and 60 g/L) were also performed at low temperature (20 and 25°C). The results confirmed that glycerol inhibits or even represses the biosynthesis of CA, depending of the temperature condition employed. The highest CA concentration value (1543 mg/L) were obtained for the cultivation at 20°C and 30 g/L glycerol, 9.2 fold-higher than run control at 30°C. The kinetics of CA degradation at pHs 6.5 and 7.5 and at different concentrations of ammonium ion (0 to 1000 mg/L) were also evaluated. It observed that the degradation was highest at pH 7.5 and higher concentration of ammonium ion. For all proposals of cultivations for CA production, it was obtained a maximum CA concentration in fermentation broth of about 1.5 g/L, indicating that CA acts as an inhibitor of its own biosynthesis. Then, the potential CA removal from broth culture was evaluated by using of alternative adsorbents such as activated carbon, clinoptilolite calcined hydrotalcite, and an ion exchange resin Amberlite IRA 400, for application in extractive fermentation process. The use of resin IRA 400 as an adsorbent to remove CA during cultivation resulted in an increase of 48% in maximum CA concentration if compared with cultivation at the same temperature condition (20°C) and glycerol concentration (15 g/L) conducted without product removal, confirming the hypothesis of inhibition by product in the CA production process. In cultivation at 20°C with glycerol concentration of 30 g/L and product removal, it was obtained a highest CA production of 2841 mg/L. The results indicate that the use of low temperature combined with the removal of product during the production process of AC represent a new and effective strategies to greatly increase the yield of CA.
Strategies for improving clavulanic acid production by Streptomyces clavuligerus
Keywords: Engenharia bioquímica; Ácido clavulânico; Streptomyces clavuligerus; Fermentação; Degradação; Clavulanic acid; Streptomyces clavuligerus; Temperature; Degradation; Extractive fermentative; ENGENHARIAS::ENGENHARIA QUIMICA